Religious Hybridity of Asian Diaspora: A Postcolonial Criticism on The Buddha of Suburbia and Anita and Me - Fajar, Yusri (Fakultas Bahasa dan Seni, 2023)
This article investigated the negotiation of Islamic and Hindu beliefs held by South Asian immigrants in British society, which resulted in religious hybridity as depicted in two diasporic fictions, The Buddha of Suburbia by Hanif Kureishi and Anita and Me by Meera Syal. This was a qualitative study. Data was collected through document studies of the two novels. The data were then analyzed using content analysis techniques in conjunction with cultural hybridity theory. The findings indicated that the religious practices of the British Asian diaspora were ambiguous. On the one hand, they continued to practice Islam and Hinduism, while on the other, they attempted to reconcile their religious beliefs with the religious, social, and cultural aspects of British society.